2019
DOI: 10.14475/kjhpc.2019.22.3.117
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Competencies Required of Undergraduate Nursing Students in Korea

Abstract: A resolution adopted by the World Health Assembly in 2014 stated that all nurses should be equipped with palliative care skills in order to integrate palliative care into a day-today healthcare system. This article introduces the palliative nursing competency that was developed for the Korean environment by the Korean Hospice Palliative Nursing Research Network based on its study of overseas cases where this competency and competency-based training were developed. This is the first step towards the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The study identified the attributes of end-of-life care competency as comprehensive symptom management, effective communication, situational response, patient-centered care, resource management, demonstrating leadership, information provision and education, and professional development. The results of this study were similar to those of the research conducted by Korean Hospice Palliative Nursing Research Network et al [17] on the palliative care competencies required of undergraduate nursing students in Korea. However, more specific attributes were identified in this study; it was observed that performing bereavement nursing, including aspects such as loss and mourning, is challenging due to work environment factors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The study identified the attributes of end-of-life care competency as comprehensive symptom management, effective communication, situational response, patient-centered care, resource management, demonstrating leadership, information provision and education, and professional development. The results of this study were similar to those of the research conducted by Korean Hospice Palliative Nursing Research Network et al [17] on the palliative care competencies required of undergraduate nursing students in Korea. However, more specific attributes were identified in this study; it was observed that performing bereavement nursing, including aspects such as loss and mourning, is challenging due to work environment factors.…”
Section: Discussionsupporting
confidence: 89%
“…In a domestic study, the competencies required to provide terminal patient care to improve the quality of life of terminally ill patients were divided into the areas of hospice palliative care principles, communication, individual nursing, self-management, and ethical practice, and were described as terminal pa-tient nursing competencies [17]. Nurses in long-term care hospitals need integrated nursing competencies, including emotional and spiritual support for end-of-life patients and their families, management of physical symptoms, continuity of care, and skills in decision-making and communication, which are not limited to imminent end-of-life situations [19].…”
Section: ) End-of-life Care Competency In Nursingmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest-scoring items in the 3 sub-categories of the children and adolescent category related to the needs concerning PPC were “the perception of being loved” in the psychosocial care sub-category, “spiritual comfort” in the spiritual care sub-category, and “alleviating pain” in the physical care category. For children and adolescents, death and end-of-life are psychosocially uncomfortable situations, and patients typically fear the dying process [ 23 ]. It is crucial for healthcare providers to help patients be able to recognize that they are loved and important to their families and spend their final moments peacefully and comfortably.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than clinical nurses exclusively providing PPC, a separate, dedicated team is required. Moreover, while the suggested timing of intervention and referral to PPC has been suggested as when the predicted survival time is fewer than 6 months according to the Patient Protection and Affordable Care Act [ 23 ], in this study, many of the participants suggested “a few weeks or a few days remaining until death” as the recommended timing. This response may be based on the social perceptions that children and adolescents are less likely to die or the fact that the PPC pilot program had only been in place for approximately 3 years at only 10 institutions, resulting in insufficient awareness.…”
Section: Discussionmentioning
confidence: 99%